1995
DOI: 10.1073/pnas.92.11.4867
|View full text |Cite
|
Sign up to set email alerts
|

SPC3, a synthetic peptide derived from the V3 domain of human immunodeficiency virus type 1 (HIV-1) gp120, inhibits HIV-1 entry into CD4+ and CD4- cells by two distinct mechanisms.

Abstract: The third variable region (V3 loop) of gpl20, the HIV-1 surface envelope glycoprotein, plays a key role in HIV-1 infection and pathogenesis. Recently, we reported that a synthetic multibranched peptide (SPC3) containing eight V3-loop consensus motifs (GPGRAF) inhibited HIV-1 infection in both CD4+ and CD4-susceptible cells. In the present study, we investigated the mechanisms of action of SPC3 in these cell types-i.e., CD4+ lymphocytes and CD4-epithelial cells expressing galactosylceramide (GalCer), an alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
5
39
0
1
Order By: Relevance
“…The above phenomenon of enhanced proliferation was observed in 28 out of 30 donors tested, indicating that it is a highly reproducible event and clearly associated with the immobilised V3, as none of the other formulations had such an impact on T cell activation. Our results concur with similar observations that multi-branched GPGRAF peptides appeared to mimic part of the V3 loop and interact with host cells, in contrast to soluble peptides which had no such effect (17). The observations of both Yahi et al (17) together with our own strongly suggest a multiple interaction of V3 with the cell target.…”
Section: Lipov3/tt Liposomes Induce An Antigen-specific Proliferationsupporting
confidence: 95%
“…The above phenomenon of enhanced proliferation was observed in 28 out of 30 donors tested, indicating that it is a highly reproducible event and clearly associated with the immobilised V3, as none of the other formulations had such an impact on T cell activation. Our results concur with similar observations that multi-branched GPGRAF peptides appeared to mimic part of the V3 loop and interact with host cells, in contrast to soluble peptides which had no such effect (17). The observations of both Yahi et al (17) together with our own strongly suggest a multiple interaction of V3 with the cell target.…”
Section: Lipov3/tt Liposomes Induce An Antigen-specific Proliferationsupporting
confidence: 95%
“…The characteristics of SPC 3 binding were assessed on lymphoid cells in which virus/cell fusion [11] and HIV infection [6,9] are inhibited by SPC 3 . We reported that SPC 3 binding reached equilibrium within 30 min [10].…”
Section: Binding Of Spc 3 To Cell Membranementioning
confidence: 99%
“…Sensitivity of SPC 3 to the lysosome content Cells (60U10 6 ) were homogenized on ice in PBS pH 7, 0.25 M sucrose. Plasma membranes and nuclei were removed by centrifugation (4 min; 3000Ug; 2³C).…”
Section: Receptor Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) Multibranched V3 synthetic peptides including the consensus hexameric motif of HIV-1 GPGRAF inhibited gp120 binding to GalCer and HIV-1 infection of intestinal cells (22). Curiously, these peptides were also characterized as inhibitors of HIV-1 and HIV-2 infection in CD4 ϩ lymphocytes and macrophages (23). Since they were designed to mimic the V3 loop and potentially act as molecular decoys for the V3 loop binding sites on the target of CD4 ϩ cells, our first interpretation was that the multibranched V3 peptides could bind to the HIV-1 coreceptors CXCR4 or CCR5.…”
mentioning
confidence: 99%